2018
DOI: 10.1017/s0032247418000591
|View full text |Cite
|
Sign up to set email alerts
|

A decade of shaping the futures of polar early career researchers: A legacy of the International Polar Year

Abstract: The Association of Polar Early Career Scientists (APECS) is an important legacy of the International Polar Year (IPY). APECS continues to foster engagement in education, outreach and communication (EOC) activities relating to the polar regions and provide training for early career researchers (ECRs). We highlight opportunities for training, leadership and skills development, such as the annual Polar Weeks and Antarctica Day celebrations. Participation and engagement in EOC activities actively contributes to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…For the ICYS survey, a call for participation was sent out via the ICYS internal email list (58 members) in September 2019. The response rate (n = 13) corre- sponds to approximately 22 % of the members, comparable to and slightly higher than similar surveys conducted among ECN (Hindshaw et al, 2018). Although the absolute number of responses may limit to some extent the representativeness of the survey, we found that the participants provided a good representation of the general membership structure of ICYS: They were split among postdocs (46 %), PhD students (46 %), faculty (one response) and gender (38 % male and 62 % female).…”
Section: Evaluating the Scope Of An Ecn With Respect To Member Expectsupporting
confidence: 70%
See 1 more Smart Citation
“…For the ICYS survey, a call for participation was sent out via the ICYS internal email list (58 members) in September 2019. The response rate (n = 13) corre- sponds to approximately 22 % of the members, comparable to and slightly higher than similar surveys conducted among ECN (Hindshaw et al, 2018). Although the absolute number of responses may limit to some extent the representativeness of the survey, we found that the participants provided a good representation of the general membership structure of ICYS: They were split among postdocs (46 %), PhD students (46 %), faculty (one response) and gender (38 % male and 62 % female).…”
Section: Evaluating the Scope Of An Ecn With Respect To Member Expectsupporting
confidence: 70%
“…The goals of APECS are to foster the development of international and interdisciplinary collaborations among ECS, to provide support in career development to ECS working in the polar regions and the cryosphere, and to promote education and outreach. The activities and scope of APECS are documented in detail on the APECS website and in a number of publications (Baeseman and Pope, 2011;APECS, 2016;Hindshaw et al, 2018;Xavier et al, 2018). Today APECS has established Memoranda of Understanding as well as informal relationships with many international organisations involved in Arctic, Antarctic, alpine and cryosphere research, education and outreach.…”
Section: An Inter-disciplinary Platform: the Association Of Polar Earmentioning
confidence: 99%
“…We argue that the IPY played a key role in stimulating such a community and sub-field, from here on referred to as "polar EOC", which continues to this day. For example, IPY spurred the creation of APECS and PEI, both of which continue to play an active role in supporting a range of research scientists and educators in their efforts to connect polar science and society (Hindshaw et al, 2018;Provencher et al, 2011;Roop et al, 2019). The unique aspects that define "polar EOC" include it being (a) geographically focused rather than focused on a discipline, mission, message/behaviour change or audience; (b) largely volunteer driven but closely associated with professional educators and communicators, with substantial institutional support on international, national and local levels; (c) stimulated by a long history of IPYs, all of which have had some kind of ongoing legacy (this was the fourth; the others started in 1882, 1932 and 1957, respectively); (d) focused on research that is cross-disciplinary, logistically challenging and expensive to carry out (hence potentially benefitting more than other fields from a collaborative and collective approach).…”
Section: Contextualising Ipy Eoc In Science Communication Literaturementioning
confidence: 99%
“…In this collection, the ongoing legacy of IPY EOC is most clearly evidenced by four papers about networks or initiatives established during IPY. The activities and process of maturation of the APECS, PYRN and PEI, 10 years on, are documented by Hindshaw et al (2018), Tanski et al (2019, this issue) and Roop, Wesche, Azhinhaga, Trummel, and Xavier (2019, this issue), respectively, while Xavier, Azinhaga, Seco, and Fugmann (2018) provide an analysis of International Polar Weeks from a Portuguese perspective. International Polar Days and Weeks were an initiative started during the IPY as a mechanism for ongoing engagement with a broad community of educators and communicators around the world.…”
mentioning
confidence: 99%